2008
DOI: 10.1007/s10865-008-9170-7
|View full text |Cite
|
Sign up to set email alerts
|

Revision and validation of the medication adherence self-efficacy scale (MASES) in hypertensive African Americans

Abstract: Background To date, no studies have validated the Medication Adherence Self-Efficacy Scale (MASES) in an independent sample of hypertensive African Americans. Purpose The purpose of this study was to revise and assess the validity of the MASES. Methods Study sample included 168 African Americans followed in primary care practices. Mean age was 54 (SD = 12.36); 86% was female; and 76% reported high school education or greater. Participants provided demographic information; completed the MASES, self-report a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 27 publications
4
131
2
5
Order By: Relevance
“…9 Self-efficacy for medication adherence was measured using the 13-item revised Medication Adherence Self-Efficacy Scale (MASES-R), with each item rated using a four-point Likert scale. 8 For all questionnaires, higher scores reflect greater adherence, stronger beliefs and greater self-efficacy, respectively; in addition, previous research has confirmed the validity and reliability of these tools. [7][8][9][10][11] Permission to use these questionnaires was obtained from the relevant developers, including permission to use the Arabic versions of the tools.…”
Section: Methodsmentioning
confidence: 68%
See 4 more Smart Citations
“…9 Self-efficacy for medication adherence was measured using the 13-item revised Medication Adherence Self-Efficacy Scale (MASES-R), with each item rated using a four-point Likert scale. 8 For all questionnaires, higher scores reflect greater adherence, stronger beliefs and greater self-efficacy, respectively; in addition, previous research has confirmed the validity and reliability of these tools. [7][8][9][10][11] Permission to use these questionnaires was obtained from the relevant developers, including permission to use the Arabic versions of the tools.…”
Section: Methodsmentioning
confidence: 68%
“…8 For all questionnaires, higher scores reflect greater adherence, stronger beliefs and greater self-efficacy, respectively; in addition, previous research has confirmed the validity and reliability of these tools. [7][8][9][10][11] Permission to use these questionnaires was obtained from the relevant developers, including permission to use the Arabic versions of the tools. Only the BIPQ and MASES-R questionnaires were translated to Arabic by the researchers themselves; this was done using previously described translation methods.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations